Design and Development of La0.5sr1.5mno4 Coated Defect Rich Tiox as an Efficient Electrocatalyst for Direct Production of Methane ch4 Via Electrochemical H2o/Co2 Co Splitting - Herrera-Diaz, F; Herrera-Diaz, F (Elsevier Ltd, 2025)
The co-splitting of water (H2O) and carbon dioxide (CO2) into hydrocarbons as a fuel is one of the major challenges in the energy and environmental applications. To overcome the challenge, the scientific research community paid great attention on the design and development of novel electrocatalysts. Herein, a perovskite type La0.5Sr1.5MnO4 coated defect-rich TiOx electrocatalyst was developed using the facile chemical co-precipitation, electrochemical anodization, and cathodization methods. The crystal structure, morphology, and elemental composition were determined by XRD, SEM, TEM, and XPS techniques, respectively. Furthermore, the electrochemical studies were carried out to investigate the performance of La0.5Sr1.5MnO4 perovskite-coated defect-rich TiOx in 1 M KOH using the linear sweep voltammetry, chronoamperometry, and impedance techniques. The electrocatalyst demonstrated the onset potentials of 1.4 V and −1.7 V for water splitting and CO2 splitting, respectively, and also showed the stability for 5 hrs. The perovskite-based transition metal oxide electrocatalyst exhibit a good response for water splitting and CO2 splitting (co-splitting) at room temperature. © 2025 Elsevier Ltd